For this, I will be using the elimination method. So with this, subtract the second equation from the first equation to get
. From here you can solve for x.
For this equation, just divide both sides by 7, and your first answer is
![x=-6](https://img.qammunity.org/2019/formulas/mathematics/college/9vfi9ksk9lpxbfi6umxlzs1r7thsm5ho5m.png)
Now that we have the value of x, substitute it into either equation to solve for y:
![-3(-6)-7y=-66\\ 18-7y=-66\\ -7y=-84\\ y=12\\ \\ -10(-6)-7y=-24\\ 60-7y=-24\\ -7y=-84\\ y=12](https://img.qammunity.org/2019/formulas/mathematics/college/o0nkyg59oxsb9c280bs645hdztsukxafy3.png)
In short, x = -6 and y = 12.